Mechanical behaviour slenderness ratio of 13 solid wall panels under uniformly distributed load - Amir Khomeiny Ruslan,; Noorsuhada Md Nor,; Muhammad Akram Ramle,; Amril Hadri Jamaludin,; Soffian Noor Mat Saliah,; Mohd Azrizal Fauzi,; Ahmad Syauqi Md Hassan,; Muhammad Afiq Tambichik,; Nor Azlina Kasim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Recently, there has been a lot of research in the concrete industry on a sustainable approach using concrete waste as a substitute for natural aggregates. The reason for this is that the quantities of construction and demolition waste generated today pose a significant threat to the environment but can be used as a useful concrete material in the construction industry. The aim of this study is therefore to investigate the mechanical behaviour of solid concrete wall panels containing recycled concrete aggregates as a partial substitute for natural fine aggregates. Mortar cubes and wall panels with dimensions of 50 mm x 50 mm x 50 mm and 1000 mm x 300 mm x 75 mm, respectively, were produced. The wall panels were made from a 1:4 concrete mix consisting of 50% recycled concrete and 5% perlite (to reduce the weight of the concrete, and improve its workability), and 1% superplastizer, while the control wall was made with 100% natural fines. The wall panels were subjected to a compression test under uniformly distributed load. The cube samples were tested at 28 days of age. Mortar cubes with RCA achieved the highest compressive strength of 16.27 MPa compared to the control sample. The control wall panel has a higher ultimate load of 147.51 kN compared to the sample that contains RCA and perlite, which has an ultimate load of 128.68 kN. By 2030, our country needs to achieve sustainable management and efficient use of natural resources. By recycling this solid waste through separating, cleaning and crushing the concrete waste into small particles so that it can be used as a building material to replace sand. This shows that recycled concrete aggregate can be a potential material for making wall panels.